2015
DOI: 10.1177/230949901502300124
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Outcome of Total Knee Arthroplasty in Obese Patients

Abstract: The MEDLINE database was searched using the key words: 'obesity' and 'knee arthroplasty'. 41 articles focused on the topic were reviewed; most studies were prospective case series (providing low-level evidence) and 3 were systematic reviews. 16 studies reported no adverse association between obesity and total knee arthroplasty (TKA) outcome, whereas 24 studies reported a poorer TKA outcome in obese patients. In the 3 systematic reviews, obesity was reported to adversely affect the outcome, the rate of complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Regarding the impact of BMI on joint awareness, Behrend et al observed a significantly inferior FJS‐12 in the younger obese female patients following TKA [6]. Many systematic reviews also found an inferior outcome, higher complication rate, increased cost, and lower survivorship in obese patients after TKA; however, the findings were relevant to BMI of > 40 kg/m 2 [16, 43]. None of the studies recruited in this meta‐analysis had evaluated this category of patients; hence, selection bias was avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of BMI on joint awareness, Behrend et al observed a significantly inferior FJS‐12 in the younger obese female patients following TKA [6]. Many systematic reviews also found an inferior outcome, higher complication rate, increased cost, and lower survivorship in obese patients after TKA; however, the findings were relevant to BMI of > 40 kg/m 2 [16, 43]. None of the studies recruited in this meta‐analysis had evaluated this category of patients; hence, selection bias was avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of previous studies of obesity and recovery following total knee arthroplasty have been mixed, with some studies suggesting that obesity is associated with worse pain and function and lower satisfaction following total knee arthroplasty, and others finding no association, or even that obese patients are more likely to be satisfied with their surgery [19][20][21][22][23][24]26,37,38 . This variability may be due to differences in the health status of the cohorts or differences in the cutoffs used to define categories of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, studies have not always reported or sub-classified subjects by comorbidities such as diabetes, hypertension, cardiac disease, or sleep apnea, each of which independently impacts surgical infection and complication rates 65,74 . For example, diabetes may double the infection risk independent of obesity 81,83 . This inability to account for comorbidities is identified as a limitation in several of the systematic reviews 44,46,47,75 .…”
Section: Limitations In Current Evidencementioning
confidence: 99%